Furosemide's one little hydrogen atom: NMR crystallography structure verification of powdered molecular organics. Issue 40 (26th April 2016) - Widdifield, Cory M.; Robson, Harry; Hodgkinson, Paul
Abstract : The potential of NMR crystallography to verify molecular crystal structures deposited in structural databases is evaluated, with two structures of the pharmaceutical furosemide serving as examples. Abstract : The potential of NMR crystallography to verify molecular crystal structures deposited in structural databases is evaluated, with two structures of the pharmaceutical furosemide serving as examples. While the structures differ in the placement of one H atom, using this approach, we verify one of the structures in the Cambridge Structural Database using quantitative tools, while establishing that the other structure does not meet the verification criteria.